Virulence genes and resistance to antibiotics of beta-hemolytic streptococci isolated from children in Chiapas, Mexico - Gutiérrez-Jiménez, Javier; Mendoza-Orozco, Mónica Ivonne; Vicente-Serrano, Alejandra; Luna-Cazáres, Lorena Mercedes; Feliciano-Guzmán, José Manuel; Girón-Hernández, Jose Antonio; Vidal, Jorge Eugenio (The Journal of Infection in Developing Countries, 2018)
Introduction: Among beta-hemolytic streptococci, Streptococcus pyogenes causes a wide variety of human disease including pharyngitis, necrotizing fasciitis and streptococcal toxic syndrome. Group A Streptococcus (GAS) uses a variety of virulence traits to colonize and then cause damage to the host; others species of beta-hemolytic streptococci are considered as emerging pathogens for humans. Despite its recognized virulence, only few studies have investigated virulence factors of GAS strains isolated in Mexico. Methodology: We conducted an epidemiological study to investigate the prevalence of GAS strains in child illnesses in Chiapas Mexico. Virulence genes encoding proteases, DNases, superantigens, as well as susceptibility to antibiotics were investigated. Results: During 2010, 2013 and 2014, beta-hemolytic streptococci (N=12) were isolated from cases of bacterial infections including pharyngitis and bacteremia, with a prevalence of 0.42, 0.04 and 0.20%, respectively. S. pyogenes was the most frequent species (33%) followed by S. agalactiae and S. dysgalactiae subsp. equisimilis (25%, each). Most GAS strains encoded genes for proteases: scpA, speB, spyCEP and mac (75%), followed by sdaD and sdaB (DNases) (50%), speA and speG (superantigens; 50 and 25%, respectively). The scpA gene was amplified in all S. agalactiae strains and in ~35% of SDSE strains. Strains were all susceptible to beta-lactams, cephalosporins and quinolones. Conclusions: The present study provides evidence on the epidemiology of beta-hemolytic streptococci infecting children at the southeast Mexico, their virulence traits and sensitivity to first-line antibiotics.